Landscape-Level Effects of Forest on Pollinators and Fruit Set of Guava (Psidium guajava L.) in Orchards across Southern Thailand - Hansen, Katrine; Sritongchuay, Tuanjit; Bumrungsri, Sara; Simmons, Benno I.; Strange, Niels; Dalsgaard, Bo (Diversity (Basel), 2020)
Pollination by wild pollinators is a key ecosystem service threatened by anthropogenic-induced land-use change. The proximity to natural habitat has previously been shown to positively affect pollinator communities and improve crop yield and quality but empirical evidence is limited from most parts of the World. Here, across six farms in Southern Thailand, we investigated the significance of landscape-level effects of natural habitat (proportion of and distance to evergreen forest) on both visitation rate and richness of pollinators as well as fruit set of guava (Psidium guajava L.), a local economically-important crop in the tropics. Overall, the most abundant pollinator was the Asian honey bee Apis cerana (39% of all visits) and different species of stingless bees (37%). We found that pollinator richness was unrelated to the proportion and distance to evergreen forest, however, the proportion of forest within a 1, 5 and 10 km radius had a significant positive impact on visitation rate of wild pollinators. Still, neither the various forest parameters nor pollinator visitation rate showed a significant impact on fruit set of guava, perhaps because guava self-pollinates. This illustrates that landscape-level degradation of natural habitat may negatively impact pollinator communities without diminishing the crop yield of the farmers.